2016
DOI: 10.1016/j.cam.2016.01.050
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive mixed-hybrid and penalty discontinuous Galerkin method for two-phase flow in heterogeneous media

Abstract: In this paper, we present a hybrid method, which consists of a mixed-hybrid finite element method and a penalty discontinuous Galerkin method, for the approximation of a fractional flow formulation of a two-phase flow problem in heterogeneous media with discontinuous capillary pressure. The fractional flow formulation is comprised of a wetting phase pressure equation and a wetting phase saturation equation which are coupled through a total velocity and the saturation affected coefficients. For the wetting phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…It can be observed that the capillary pressure functions are essentially in agreement with the experimental data. The capillary pressure curves clearly demonstrate that the capillary pressure functions are non-convex functions with respect to the saturation S w , and thus the conventional convex functions [2,[4][5][6][7]16] for the capillary pressure would not agree with the experimental data.…”
Section: Impes Methods For the Discrete-fracture Modelmentioning
confidence: 90%
See 1 more Smart Citation
“…It can be observed that the capillary pressure functions are essentially in agreement with the experimental data. The capillary pressure curves clearly demonstrate that the capillary pressure functions are non-convex functions with respect to the saturation S w , and thus the conventional convex functions [2,[4][5][6][7]16] for the capillary pressure would not agree with the experimental data.…”
Section: Impes Methods For the Discrete-fracture Modelmentioning
confidence: 90%
“…The classical two-phase flow models [2,[4][5][6][7] have been developed based on the single-phase flow model through introducing several new quantities, such as saturation, relative permeability, and capillary pressure. Relative permeability considerably effects on oil and water two-phase flows in porous media.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been used to simulate two-phase flow, such as the finite element method, 2 the finite volume method, [2][3][4][5] mixed finite element methods, 2,6,7 and discontinuous Galerkin methods. 2,[8][9][10][11][12][13][14][15][16][17] Recently, many efforts have been focused on applying high-order methods to these kind of problems due to their advantages.…”
Section: Introductionmentioning
confidence: 99%
“…In [29,30,44], decoupled solution using a mixed finite element method for the pressure equation and an explicit or semi-implicit DG method for the saturation equation were studied. In [36], decoupled DG methods with interior penalties and upwinding schemes were applied to the original formulation while the pressure equation is obtained by summing the discretized conservation equations of two phases.…”
Section: Introductionmentioning
confidence: 99%